The Effect of Fasting on the Concentration of Enzimatic Antioxidants (Superoxide Dismutase and Glutathione Peroxidase) in Rats - Jannah, Muliatul; Nasihun, Taufiqurrahman; Sumarawati, Titiek (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2016)
Introduction: Consumption of excessive calories can increase the incidence of degenerative diseases mediated by ROS. Caloric restriction, have been shown to increase levels of antioxidants superoxide dismutase (SOD) and Gluthatione Peroxidase (GPx). Fasting like Ramadan fasting (FLRF) is a form of calorie restriction, but its effect on levels of SOD and GPx remains unclear. Objectives: to investigate the effect of fasting on levels of SOD and GPx. Methods: in a post-test only control group design, sample of 24 rats Sprague Dawley Rats aged 3-month-old, weighing 250-300 grams, were randomly divided into 4 groups. Group 1 (P-70), 2 (P-100), and 3 (P-140) were fasted for 6 hours/day, each group received of 70%, 100% and 140% calories respectively. Group 4 (C-AL) received 100% calories, ad libitum. Day 16 blood was taken and levels of SOD and GPx were determined by ELISA. Data were analyzed using one-way ANOVAs, followed by post hoc LSD tests, p<0.05 was considered statistically significant. Results: the results showed that the levels of SOD and GPx occur significant differences between the groups, p = 0.000. The test results post hoc SOD (318.64) and GPx (89.16) group P-70, compared with group C-AL (278.60 and 57.20) was significantly higher (p = 0.00). SOD and GPx P-70 group compared with the group P-140 (92.03 and 48.79), significantly higher (p = 0.00). Compared with group P-100 (296.70 and 75.71) SOD and GPx in group P-70 was significantly higher, p = 0.000. Conclusion: Fasting with calorie intake of 70% and 100% for 15 days can increases levels of SOD and GPx in male rats.